Estudo e implementação de widgets acessíveis para web - Oliveira, Antonio Vanderlei Rosa de (2014)
This work presents an approach to the study of standards and guidelines related to Web accessibility, defined by the agency that regulates the Web, the W3C. Discusses the concepts of Ajax, Widgets, among others, as well as their relationship with the so-called RIA – Rich Internet Application. Presents the concepts of WCAG 2.0, ARIA – Accessible Rich Internet Applications and W eb accessibility, demonstrating how it works. Discusses the study of the ARIA specification, as well as its relationship with the screen reader NVDA – NonVisual Desktop Access and the TabPanel Widget. Shows the development performed by members of this work of TabPanel Widgets and the results obtained with these implementations. Presents the concepts of jQuery, jQuery-UI and Github, as well as contribution made to the jQuery-UI with corrections in your source code related to ARIA, bringing the results of this implementation. Shows a study on the most popular websites in the world, which aims to assess the accessibility of Widgets in them.